Estructura interna y diferenciación social urbana: comuna de La Reina - Franco de la Jara, Eliana; Ortiz Véliz, Jorge (Investigaciones Geográficas: Una mirada desde el sur, 1983)
Land value and the role of the private management have been traditionally considered as explanatory forces of the socio-spatial differenciaton of the urban environment. However, in Chilean cities - specially those which have had a growing metropolization process - shouldbe added state’s influence through housing programs for middle and low social sectors, some of them do not having access to formal housing market. Three patterns of social differenciation were identified, starting from size, quality, state of maintenance, building year, land value, state role and action of neighboring groups: a) Consolidated urban area, characterized by its social heterogeneity; b) transitional-expansional urban area, defined by its high status of social homogeneity,and c) peripheral-consolidated urban area of low economical status. Special emphasis is put on the third category, which has been calleds ubintegrated habitat. ln fact, in front of the apparent homogeneity of this sector, it is possible indetify some social differences, specially from the point of view of the works status of the inhabitants, which are a product of the housing problem management in this space.